2017
DOI: 10.1111/gbi.12236
|View full text |Cite
|
Sign up to set email alerts
|

Paleoecology and paleoceanography of the Athel silicilyte, Ediacaran–Cambrian boundary, Sultanate of Oman

Abstract: The Athel silicilyte is an enigmatic, hundreds of meters thick, finely laminated quartz deposit, in which silica precipitated in deep water (>~100-200 m) at the Ediacaran-Cambrian boundary in the South Oman Salt Basin. In contrast, Meso-Neoproterozoic sinks for marine silica were dominantly restricted to peritidal settings. The silicilyte is known to contain sterane biomarkers for demosponges, which today are benthic, obligately aerobic organisms. However, the basin has previously been described as permanently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 122 publications
(285 reference statements)
5
21
1
Order By: Relevance
“…Aerobic methanotrophy, being an energetically favored process (Megonigal, Hines, & Visscher, 2004) Figure S1). These results are in contrast to previous work of Grosjean et al (2009) and Stolper et al (2017), where C 31 3-methylhopane was identified as a significant peak. Based on a re-evaluation of previously published data and a comparison with standards, we attribute this to the superior separation capability of the DB-5MS GC column and the specificity of the QQQ detection that combine to minimize co-elution of the 3β-methylhopane with βα-homohopane isomers and methylgammacerane.…”
Section: Redox Conditions and Corresponding Biological Indicatorscontrasting
confidence: 99%
See 2 more Smart Citations
“…Aerobic methanotrophy, being an energetically favored process (Megonigal, Hines, & Visscher, 2004) Figure S1). These results are in contrast to previous work of Grosjean et al (2009) and Stolper et al (2017), where C 31 3-methylhopane was identified as a significant peak. Based on a re-evaluation of previously published data and a comparison with standards, we attribute this to the superior separation capability of the DB-5MS GC column and the specificity of the QQQ detection that combine to minimize co-elution of the 3β-methylhopane with βα-homohopane isomers and methylgammacerane.…”
Section: Redox Conditions and Corresponding Biological Indicatorscontrasting
confidence: 99%
“…The existence of sulfidic waters during deposition of SOSB sediments is supported by trace element data from Schroder and Grotzinger (2007) and Wille, Nägler, Lehmann, Schröder, and Kramers (2008), through sulfur isotopic analyses of sulfur species by Grotzinger (2008, 2010), and the biomarker studies of Grosjean et al (2009) and Stolper et al (2017). The hydrocarbon biomarker patterns evident in our analysis are entirely consistent with this, further suggesting sulfate reduction was pervasive in the Athel deep basin.…”
Section: Redox Conditions and Corresponding Biological Indicatorssupporting
confidence: 81%
See 1 more Smart Citation
“…The abundance ratio of the major (C 27 –C 35 ) hopanes to (C 27 –C 29 ) regular steranes provides a direct and informative measure of the relative contributions of bacteria and eukaryotes to sedimentary organic matter, which has proved useful to track the evolving Proterozoic surface ocean ecology. A temporal step change occurs as sterane/hopane (S/H) ratios shift from values of approximately zero (0.00) throughout the Paleoproterozoic and Mesoproterozoic as revealed by a dearth of eukaryotic steranes (Blumenberg et al, ; Brocks et al, , , ; Flannery & George, ; Gueneli et al, ; Isson et al, ; Luo et al, ; Nguyen et al, ; Suslova et al, ) before obviously increasing significantly during the Cryogenian and Ediacaran Periods (Brocks et al, ; Grosjean et al, ; Love et al, ; Stolper et al, ). In some cases, these can attain Phanerozoic average S/H range of ~0.5–2.0 for sedimentary rocks and oils, although bacterially dominated Ediacaran biomarker assemblages (with S/H values < 0.1) are also found in other locations and can feature for tens of millions of years (Pehr et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The 'death mask' and silicification hypotheses outlined above have distinct and important implications for our understanding of late Ediacaran marine biogeochemistry. The silicification hypothesis implies that silica was concentrated enough in the Ediacaran oceans to precipitate very near the seafloor in subtidal settings, despite known Ediacaran subtidal cherts generally being not primary but replacive after carbonate, and abundant subtidal cherts and silicilytes appearing only across the Ediacaran-Cambrian boundary (post-dating deposition of the Ediacara Member; Siever, 1992;Maliva et al, 2005;Brasier et al, 2011;Perry and Lefticariu, 2014;Dong et al, 2015;Stolper et al, 2017). Conversely, the 'death mask' hypothesis implies that the decay and mineralization of widespread microbial matgrounds could have contributed to the high pyrite burial flux inferred for Ediacaran marine sediments (Liu, 2016;Shields, 2018).…”
Section: Introductionmentioning
confidence: 99%